2023
DOI: 10.1038/s41420-023-01350-z
|View full text |Cite
|
Sign up to set email alerts
|

Stomatin-like protein 2 deficiency exacerbates adverse cardiac remodeling

Abstract: Myocardial fibrosis, oxidative stress, and autophagy both play key roles in the progression of adverse cardiac remodeling. Stomatin-like protein 2 (SLP-2) is closely related to mitochondrial function, but little is known about its role and mechanism in cardiac remodeling. We developed doxorubicin (Dox), angiotensin (Ang) II, and myocardial ischemia-reperfusion (I/R) injury induced cardiac remodeling model and Dox treated H9C2 cell injury model using SLP-2 knockout (SLP-2-/-) mice and H9C2 cells with low SLP-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…In this study, KEGG enrichment analysis indicated that 832 differentially expressed mRNAs were mainly involved in metabolic, NOD-like receptor, Wnt, PPAR, and p53 signaling pathways and in glycerophospholipid metabolism. The target genes of the differentially expressed miR-NAs were mainly involved in endocytosis, the PI3K-Akt signaling pathway, nucleocytoplasmic transport, MAPK signaling pathway, and viral carcinogenesis pathways, among these, the NOD-like receptor, Wnt, PPAR, PI3K-Akt, and MAPK signaling pathways were closely related to mitochondrial function [35][36][37]. For example, NODlike receptor family member X1 (NLRX1) localized to the mitochondrial outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, KEGG enrichment analysis indicated that 832 differentially expressed mRNAs were mainly involved in metabolic, NOD-like receptor, Wnt, PPAR, and p53 signaling pathways and in glycerophospholipid metabolism. The target genes of the differentially expressed miR-NAs were mainly involved in endocytosis, the PI3K-Akt signaling pathway, nucleocytoplasmic transport, MAPK signaling pathway, and viral carcinogenesis pathways, among these, the NOD-like receptor, Wnt, PPAR, PI3K-Akt, and MAPK signaling pathways were closely related to mitochondrial function [35][36][37]. For example, NODlike receptor family member X1 (NLRX1) localized to the mitochondrial outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Liu hypothesized that increased calcium transfer in the endoplasmic reticulum may lead to mitochondrial calcium overload, thereby triggering mitochondrial apoptosis [ 25 ]. Also, it is worthwhile to consider the potential involvement of RCN2, a protein that encodes multiple EF-hand Ca2+-binding proteins and has been involved in mitochondrial apoptosis [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%